Under-estimation of self-reported occupational exposure by questionnaire in hospital workers. Issue 8 (21st April 2011) - Donnay, C; Denis, M-A; Magis, R; Fevotte, J; Massin, N; Dumas, O; Pin, I; Choudat, D; Kauffmann, F; Le Moual, N
Abstract : Objectives: The aim of the study was to determine whether self-reported occupational exposure to cleaning/disinfecting agents in hospital workers is accurate, in comparison to expert assessment, taken to be the gold standard. Methods: In the Epidemiological Study of the Genetics and Environment of Asthma (EGEA), participants were interviewed on occupation with a specific questionnaire for hospital workers regarding tasks and cleaning/disinfecting agents. Two estimates of exposure were available: self-report and expert assessment. The expert assessment involved a standardised procedure to estimate intensity, frequency and probability of exposure for each job. The present analysis focused on eight exposures: formaldehyde, glutaraldehyde, bleach/chlorine, alcohol, quaternary ammonium components, ammonia, sprays and latex gloves. Agreement and differences between self-reported and expert estimates were studied by kappa and phi coefficients and McNemar tests, respectively. Results: In the survey of 1571 adults, 176 ever hospital workers (327 occupations) with both self-reported and expert exposure assessments were studied. An underestimation of self-reported exposure was observed especially for formaldehyde (26.5% vs 32.7%, p=0.01), ammonia (7.4% vs 18.8%, p<0.0001), alcohol (64.9% vs 93.0%, p<0.0001) and quaternary ammonium components (16.6% vs 70.9%, p<0.0001), compared to expert assessment. Conclusion: Occupational exposure to disinfecting/cleaning agents is common and high in hospitals. A large underestimation of self-reported exposure and a lack of knowledge of product components was observed. Our results show the relevance of expert assessment in epidemiological studies to limit measurement bias. This work underlines the need for health education programmes on the occupational risks induced by these types of products.